Determining Factors for Enhancing Accounting Information Quality in Public Service Agencies - Diptyana, Pepie; Anastasia, Nabilah Afifah; Rokhmania, Nur'aini (MBIA, 2023)
This research examines whether personnel competency, information technology (IT) utilization and government accounting standard (GAS) proficiency have influenced accounting information quality and internal control as moderates in public service agencies (PSA). We performed a quantitative method and collected data by questionnaires. We distributed The questionnaires to the chief or head of public services agencies and their financial and accounting department staff in Surabaya as Population. Despite the minimum number based on Slovin being 80, the total number of collected samples for this study is 100. SEM-PLS conducted a hypotheses test. There are three research findings: (1) IT utilization and GAS proficiency are positively significant toward accounting information quality; (2) Internal control is supported as a moderating variable, positively significant to the relationship between personnel competencies and accounting information quality. These findings imply that IT infrastructure has to be well maintained and updated to assure accounting data reliability. Public service agencies need government accounting standard expertise by hiring experts, consultants, or well-trained accounting department personnel. Finally, to enhance the accounting information systems' quality, internal control is also an essential factor in ensuring that all components in the accounting system are running well. Keywords: Accounting Information Systems, Government Accounting Standards Proficiency, Information Technology Utilization, Internal Control, Personnel Competencies Abstrak Penelitian ini bertujuan untuk menguji peran kompetensi pegawai, penggunaan teknologi informasi (TI), dan pemahaman standar akuntansi pemerintahan (SAP) dalam memengaruhi kualitas informasi akuntansi dengan pengendalian internal sebagai variabel moderasi di Badan Layanan Umum (BLU). Data dikumpulkan menggunakan kuesioner. Kuesioner didistribusikan kepada kepala BLU, serta pegawai bagian akuntansi dan keuangan di wilayah kota Surabaya sebagai populasi. Total kuesioner yang dapat diolah adalah sejumlah 100. Jumlah ini telah memenuhi syarat pengolahan data karena melebihi 80 (jumlah minimum sampel berdasarkan perhitungan slovin). Hipotesis diuji dengan SEM-PLS. Hasil riset ini menemukan bahwa : (1) penggunaan TI dan pemahaman SAP berpengaruh signifikan positif terhadap kualitas informasi akuntansi; dan (2) Pengendalian internal terbukti signifikan memoderasi pengaruh kompetensi sumber daya manusia dan kualitas informasi akuntansi. Dengan demikian, BLU perlu menjaga dan memperbarui infrastruktur TI agar dapat memelihara reliabilitas data dan proses akuntansi, mempekerjakan tenaga ahli yang memahami SAP baik dengan cara melatih pegawai atau bersama konsultan SAP. Pengendalian internal di BLU juga penting diterapkan untuk memastikan bahwa sistem akuntansi berjalan dengan lancar. Kata Kunci: Sistem Informasi Akuntansi, Pemahaman Standar Akutansi Pemerintahan, Pemanfaatan Teknologi Informasi, Pengendalian Internal, Kompetensi Sumber Daya Manusia